A French connection; paths to a 'new system' of accounting for the Royal Navy in 1832. Issue 2 (March 2021) - McBride, Karen
Abstract: This study contextualises the official introduction of double entry bookkeeping in the Royal Navy, in 1832. The objective is to consider how accounting developed and changed through the competing logics of path dependent processes and to provide insights and explanations of those accounting changes in the Royal Navy. An innovative theoretical framework combines the longer-term lens of historical institutionalism with the roles of key actors to investigate change, logic and meaning of accounting in the Royal Navy in the context of financial reforms resulting from governmental investigations. The study is intended to make a contribution to accounting history and theory by means of this extension of historical institutionalism, exploring the options available and the paths taken at critical junctures, as the result of key players and their influence on the practices developed. The study identifies the paths available to the Royal Navy in the adoption of this 'new system' of accounting. The paper contributes to the literature on accounting development and change, on military accounting history and on the political nature of accounting in exploring the influences for change.